Math, asked by adawadi2793, 1 year ago

Wthout calculating find the value of (2-a)^3 +(2-c)^3 -3(2-a)(2-b)(2-c), if a+b+c =6

Answers

Answered by snbtsoham
0

Answer:

Step-by-step explanation:

By using the identity - a*3 + b*3 + c*3- 3abc = (a+b+c)(a*3+ b*3 +c*3-ab-bc-ac)

here a= (2-a)

       b=(2-b)

       c=(2-c)

by putting in values we get

(2-a)*3 + (2-b)*3 + (2-c)*3-3(2-a)(2-b)(2-c)=

Now you can calculate the value easily

But,by the way your question is not complete.

Similar questions